The Role of HRM Factors in Enhancing the Sustainability of Corporate Environmental Performance Mediated by Green Competencies - Khasanah, Siti Fatimatul; Yanti, Pika Meri; Efendi, Ifan (UNIVED Press, 2026)
This study aims to empirically examine the influence of Green Employee Involvement and Green Training on Corporate Environmental Performance, with Green Competencies acting as a mediating variable. The research adopts a quantitative descriptive approach, with data collected through the distribution of questionnaires. Respondents consisted of non-medical human resources working in Hospitals located in the Lubuk Linggau City and Musi Rawas Regency areas. The analytical methods employed include descriptive analysis and Partial Least Squares (PLS).The findings of the study reveal that: (1) Green Employee Involvement does not have a significant effect on Green Competencies among employees in health facilities in Hospitals located in the Lubuk Linggau City and Musi Rawas Regency areas; (2) Green Training has a significant positive effect on Green Competencies; (3) Green Competencies significantly influence the Environmental Performance of health organizations; (4) Green Employee Involvement has a significant positive impact on Environmental Performance; (5) Green Training significantly enhances Environmental Performance; (6) Green Competencies do not mediate the relationship between Green Employee Involvement and Environmental Performance; and (7) Green Competencies significantly mediate the relationship between Green Training and Environmental Performance in Hospitals located in the Lubuk Linggau City and Musi Rawas Regency areas.